Large Traumatic Pneumatocele in a 2-Year-Old Child - Cheung, N. K. (Hindawi Publishing Corporation, 2013)
Traumatic pneumatoceles are a rare complication of blunt chest trauma in children. Although they characteristically present as small, regular shaped lesions which can be safely treated nonoperatively, larger traumatic pneumatoceles pose diagnostic and management difficulties for clinicians. This case study reports one of the largest traumatic pneumatoceles reported to date in the paediatric population, which resulted in aggressive surgical intervention for both diagnostic and treatment reasons. This case adds further evidence to the current literature that significantly large traumatic pneumatoceles with failure of initial conservative management warrant surgical exploration and management to optimise recovery and prevent complications.